(untitled) (Educational Dimension, 2020)
The system of education is challenged by need to prepare a new generation of professionals who would not only master a field-required skill but also harness soft skill. The paper reviews definition and characteristics of formal, non-formal and informal education models and defines the possibilities to address the education challenges in combination of forms. The Summer school as a form of non-formal education is defined and proposed to fill the gap in formal education. The paper presents a framework of how to develop a curriculum for a summer school centered around a competency-based approach. The three key components – profile of participant, expected result, and real-life problem, form a set of skills and knowledge that define learning outcomes and shape the program. Finally, the paper reviews the case study of summer school hold in Kharkiv to demonstrate how the approach can be applied to practice. Summer school is a useful tool to establish and test new forms of education that contribute to learning process of both students and educators.